Accelerating Oxygen Electrocatalysis Kinetics on Metal–Organic Frameworks via Bond Length Optimization - He, Fan; Liu, Yingnan; Yang, Xiaoxuan; Chen, Yaqi; Yang, Cheng‑Chieh; Dong, Chung‑Li; He, Qinggang; Yang, Bin; Li, Zhongjian; Kuang, Yongbo; Lei, Lecheng; Dai, Liming; et al. (Nano-Micro Letters, 2024)
Metal–organic frameworks (MOFs) have been developed as an ideal platform for exploration of the relationship between intrinsic structure and catalytic activity, but the limited catalytic activity and stability has hampered their practical use in water splitting. Herein, we develop a bond length adjustment strategy for optimizing naphthalene-based MOFs that synthesized by acid etching Co-naphthalenedicarboxylic acid-based MOFs (donated as AE-CoNDA) to serve as efficient catalyst for water splitting. AE-CoNDA exhibits a low overpotential of 260 mV to reach 10 mA cm−2 and a small Tafel slope of 62 mV dec−1 with excellent stability over 100 h. After integrated AE-CoNDA onto BiVO4, photocurrent density of 4.3 mA cm−2 is achieved at 1.23 V. Experimental investigations demonstrate that the stretched Co–O bond length was found to optimize the orbitals hybridization of Co 3d and O 2p, which accounts for the fast kinetics and high activity. Theoretical calculations reveal that the stretched Co–O bond length strengthens the adsorption of oxygen-contained intermediates at the Co active sites for highly efficient water splitting. Highlights: 1 The acid etching Co-naphthalenedicarboxylic acid-based metal–organic frameworks (donated as AE-CoNDA) catalyst displayed an excellent oxygen evolution reaction (OER) activity for long-term stability. 2 Integration of the AE-CoNDA cocatalyst into BiVO4 achieved a remarkable PEC-OER activity. 3 The stretched Co-O bond length regulated the spin state transition at the Co active sites. 4 The optimized high spin state of Co sites adjusted the orbitals hybridization of Co 3d and O 2p.